(Dithiobenzoato-κ(2) S,S′)[hydridotris(pyrazol-1-yl-κN (2))borato](triphenylphosphine-κP)ruthenium(II) - Lin, Chia-Her (International Union of Crystallography, 2008)
Reaction of [Ru(Tp)Cl(PPh(3))(2)] (Tp = hydridotrispyrazolylborate) with ammonium dithiobenzoate in methanol leads to the formation of the title compound, [Ru(C(9)H(10)BN(6))(C(7)H(5)S(2))(C(18)H(15)P)]. In the crystal structure, the Ru atom is coordinated by three N atoms of the Tp ligand, one P atom of the triphenylphosphine ligand and the two S atoms of the dithiobenzoate ligand within a slightly distorted octahedron. The Ru—S bonds are slightly different [2.321 (1) and 2.396 (1) Å] and the average N—Ru—N angle is 86.31°.